Technocrime, policing, and surveillance - Leman-Langlois, Stéphane (Routledge frontiers of criminal justice, 2013)
Introduction / Stéphane Leman-Langlois -- The criminal ecology of payment systems how "identity theft" evolved from plastic counterfeiting to the "crime of the century" / Benoît Dupont -- Media representations of the surveilled : exploring the 'subjects of surveillance' in mainstream media and alternate press releases / Rachel Finn and Michael McCahill -- The virtual surveillance lab : the creation of a simulated experimental environment / Stéphane Leman-Langlois -- Investigating transnational cybercrime : current challenges and emerging initiatives / Frédéric Lemieux and Brian Bales -- "We don't have these laser beams and stuff like that" : police investigations as low-tech work in a high-tech world / Laura Huey and Johnny Nhan -- Technology and database expansion : what impact on policing? / Olivier Ribaux and Tacha Hicks -- Technocrime, criminology, and marshall mcluhan : towards an inventory of criminological effects / James Sheptycki